The stressors affecting teacher burnout in emergency remote teaching context - Emir, Gamze; Saral, Nesli Cigdem; Sacan, Bilge Merve; Ozmen, Kemal Sinan (Pergamon-Elsevier Science Ltd, 2023)
COVID-19 brought many challenges to teachers to maintain emergency remote teaching; however, those chal-lenges were not examined in terms of their potential to cause teacher burnout. This study scrutinized the possible stressors by employing semi-structured interviews, observations of lessons, and post-interviews with three En-glish language teachers. Adopting the constant comparison method, the study found that emergency remote teaching caused certain stressors which derived from dissatisfaction with the job, political issues, the lack of support from society, and feeling of incompetence. It provided a number of implications for teachers, policy -makers, and teacher trainers for the demands of emergency remote teaching.
Keywords: Burnout; English language teachers; Emergency remote teaching; COVID-19